A STUDY OF MASS LOSS AND DUST FORMATION NEAR HOT STARS - Kuratov, K. S.; Miroshnichenko, A. S.; Kusakin, A. V.; Alimgazinova, N. Sh.; Nuryzbaeva, A. Zh.; Manapbaeva, A. B.; Kuratova, A. K. (Одеські астрономічні публікації, 2016)
At present dust formation is well studied only near cool stars, whose surface temperatures are close to those of dust sublimation. Hot stars need to supply large amounts of circumstellar material to allow dust formation around them. Such conditions naturally exist near supergiants with masses over 25 M⊙. The theory of stellar evolution predicts that less massive stars do not provide enough matter for dust formation. Nevertheless, dust exists near dwarfs with the B[e] phenomenon and giants of A–G spectral types which do not belong to star formation regions. A large group of objects with the B[e] phenomenon with extremely strong emission-line spectra that are neither young nor highly evolved has been recently identified. They are called FS CMa type objects. Their infrared excesses imply a large amount of recently created dust. Therefore, these objects can noticeably contribute to the Galactic dust content, but they have not been taken into consideration from this perspective.